Pengaruh Pendidikan Kesehatan Tentang Perilaku Hidup Bersih Dan Sehat (Phbs) Dengan Metode Ceramah Terhadap Pengetahuan Dan Sikap Pada Anak Panti Asuhan Keluarga Yatim Muhammadiyah Surakarta - DEWI, Nur Annisa Alviana (2016)
School age children are past the age of children who are very different from adults. Survey of 10 children known that many as 50% of children have less knowledge and not undrestand the importance of PHBS, one of the problems of personal health conditions such as eating not wash their hands first. This study aimed to determine the effect of health education for knowledge and attitude of PHBS in children of Panti Asuhan Keluarga Yatim Muhammadiyah (PAKYM) Surakarta. This research method is by using a quasi-experimental design pretest-posttest control group were equipped with a quantitative approach. This research using questionnaires as research instrument. This study population is PAKYM surakarta many as 46 children. Distribution of the sample using random sampling by the division of the experimental group 23 children and the control group 23 children. Analysis of the data used is a bivariate analysis of paired samples T test. The results prove that there is no effect of health education lectures to knowledge (p=0,426) and attitude (p=0,492) of PHBS in children PAKYM surakarta. Key words : PHBS, knowledge, attitude and health education